Determination Of Work Index of Spodumene from Kenticha Ore, Southern Ethiopia - Mama Kaso, Anuwar; Kebede Nego, Bisrat (Wroclaw University of Technology, 2025)
The samples used for this study were granite and spodumene ore (2000 grams) (divided into four equal parts with 500 g), 500 g for chemical analysis, and granite (500 g) was separately used as reference ores from the Kenticha ore deposit. Each test ore was weighed at 2000 grams, and the reference ore was weighed at 500 grams, and all were ground in a lab ball mill under the same conditions. Size analysis of the feed to the ball mill and the output from the ball mill was performed on test ore and refer-ence ore, with the results properly tabulated. The feed and discharge particle sizes for the samples into the ball mill were calculated using the Gaudian–Schumann formula to ensure an 80% passing rate. The work index for spodumene ore, as cited in the literature, is found in the range of 10.4–11.5 kWh/ton. In this study, the Modified Bond Index method was used to determine the work index of spodumene samples from Kenticha ore using granite as a reference ore. The work index of the Kenticha spodumene ore was discovered to be 11.391 kWh/ton.
Mining Science, Vol. 32, 2025, s. 119-134
Keywords: mining; geology; geo-engineering